Mathematical modeling and analysis of the SARS-Cov-2 disease with reinfection. (June 2022) - Atifa, Asghar; Khan, Muhammad Altaf; Iskakova, Kulpash; Al-Duais, Fuad S.; Ahmad, Irshad
Abstract: The COVID-19 infection which is still infecting many individuals around the world and at the same time the recovered individuals after the recovery are infecting again. This reinfection of the individuals after the recovery may lead the disease to worse in the population with so many challenges to the health sectors. We study in the present work by formulating a mathematical model for SARS-CoV-2 with reinfection. We first briefly discuss the formulation of the model with the assumptions of reinfection, and then study the related qualitative properties of the model. We show that the reinfection model is stable locally asymptotically when R 0 < 1 . For R 0 ≤ 1, we show that the model is globally asymptotically stable. Further, we consider the available data of coronavirus from Pakistan to estimate the parameters involved in the model. We show that the proposed model shows good fitting to the infected data. We compute the basic reproduction number with the estimated and fitted parameters numerical value is R 0 ≈ 1.4962 . Further, we simulate the model using realistic parameters and present the graphical results. We show that the infection can be minimized if the realistic parameters (that are sensitive to the basic reproduction number) are taken into account. Also, we observe the model prediction for the total infected cases in the future fifth layer of COVID-19 in Pakistan that may begin in the second week of February 2022. Graphical Abstract: ga1 Highlights: A new mathematical for SARS-CoV-2 with reinfection is presented. Local and global asymptotical stability analysis of the model is presented. Parameters estimations for the real cases in Pakistan are presented. Numerical simulations with the predictions of future waves in Pakistan is given.